ChemInform Abstract: Preparation and Diels—Alder Reactions of 1′‐Heterosubstituted Vinylimidazoles. Issue 38 (3rd September 2015) - Ray, Abhisek; Mukherjee, Sabuj; Das, Jayanta; Bhandari, Manoj K.; Du, Hongwang; Yousufuddin, Muhammed; Lovely, Carl J.
Abstract The preparation of halogen, silyl or stannyl substituted vinylimidazoles is developed and their Diels—Alder reaction with N‐phenylmaleimide is found to give tricyclic products, however with slightly different structural results.